2013
DOI: 10.1111/jnc.12363
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and IGF1 modulate turnover of polysialylated neural cell adhesion molecule (PSANCAM) in a process involving specific extracellular matrix components

Abstract: Cellular interactions mediated by the neural cell adhesion molecule (NCAM) are critical in cell migration, differentiation and plasticity. Switching of the NCAM-interaction mode, from adhesion to signalling, is determined by NCAM carrying a particular post-translational modification, polysialic acid (PSA). Regulation of cell-surface PSA-NCAM is traditionally viewed as a direct consequence of polysialyltransferase activity. Taking advantage of the polysialyltransferase Ca 2+ -dependent activity, we demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…Using western blotting we confirmed that both antibodies label proteins in the 200-220-kDa range. Post-translational addition of different PSA chain lengths to the NCAM protein results in variable molecular weights within this range, which is consistent with previous reports of PSA-NCAM size (Mikkonen et al, 1999;Monzo et al, 2013) (Fig. 1D).…”
Section: Antibodies Are Specific For Polysialated Ncam Proteinsupporting
confidence: 92%
“…Using western blotting we confirmed that both antibodies label proteins in the 200-220-kDa range. Post-translational addition of different PSA chain lengths to the NCAM protein results in variable molecular weights within this range, which is consistent with previous reports of PSA-NCAM size (Mikkonen et al, 1999;Monzo et al, 2013) (Fig. 1D).…”
Section: Antibodies Are Specific For Polysialated Ncam Proteinsupporting
confidence: 92%
“…Pappaa could act in an autocrine manner to stimulate postsynaptic IGF1R signaling in OFF bipolar cells. Postsynaptically, IGF1 has been shown to promote dendritic growth (Camarero et al, 2001;Cheng et al, 2003;Shi et al, 2005;Carlson et al, 2014), membrane receptor and channel stability through the activity of synaptic scaffolding proteins (Corvin et al, 2012;Della Sala et al, 2016), and the development and maintenance of synaptic connections via cell adhesion molecules (Bonfanti, 2006;Monzo et al, 2013). Although we did not observe defects in dendritic size (Fig.…”
Section: Pappaa Regulates Igf1r Signaling To Promote Light Offset Resmentioning
confidence: 53%
“…A comparable interrelation was also observed in the postnatal tunica albuginea [71], which enclose the testis and consists of fibroblast, myofibroblast and smooth muscle cells and extracellular matrix components like collagen [82]. An in cellulo study by Curtis and co-workers described a possible explanation for the contrarily-regulated amounts of polysialylated NCAM and collagen [83]. They observed an internalization and desialylation of polySia-NCAM, specifically triggered by extracellular collagen.…”
Section: Polysia-ncam During the Development Of The Epididymismentioning
confidence: 60%
“…( B ) With increasing amounts of collagen the polysialylation of smooth muscle cells stops. Based on cell culture experiments in the lab of Curtis showing that collagen induces the internalization of polySia-NCAM and degradation of polySia chains [83], a functional relationship between increasing amount of collagen and decreasing amount of polySia-NCAM was discussed [71]. …”
Section: Figurementioning
confidence: 99%